Comparing and evaluating the nationally determined contributions of the top six emitters under the Paris Agreement goals. Issue 3 (3rd July 2018) - Pan, Xunzhang; Tao, Jie; Wang, Hailin
ABSTRACT: Comparing and evaluating the Nationally Determined Contribution (NDC) is an important element in global stocktake in the post-Paris climate negotiations, aimed at closing the emissions gap with the Paris Agreement goals. To date, however, there has still been no explicit guideline or method. By applying emissions allowance allocated by 16 schemes as benchmarks, this paper tries to compare and evaluate the NDCs of the top six emitters, which jointly account for about 70% of the world's CO2 emissions. Results show that the four developed countries' NDCs lack ambition with respect to most allocations under 2°C and all under 1.5°C, indicating they need to substantially ratchet up their NDCs and lead elevating mitigation. Evaluating cumulative emissions is more likely to clarify the ambition and fairness of China's NDC. If considering cumulative emissions, China's NDC is aligned with the median of cumulative allowances under 2°C and within the 1.5°C range. The Paris Agreement invited the Parties to communicate the mid-century low emissions strategies. This paper also tries to explore the mid-century mitigation in the perspective of allocations, which might provide decision-makers with some useful information when envisaging the post-NDC mitigation.